Validasi Metode Penentuang Minyak dan Lemak dalam air Laut dengan Spektrofotometri Inframerah - Gaisandry Devira Samban (JURNAL KIMIA MULAWARMAN, 2021)
Validation research method of determining oil and grease in sea water with Infrared Spectrophotometry has been conducted. To obtain valid measurement results, the research stages included measurements in the form of validation parameters such as linearity test, limit detection (LOD), quantization limit (LOQ), recovery, precision, reproducibility, detection limit of method (MDL), instrument validation and measurement uncertainty. The results showed that linearity met the good results with a correlation coefficient (R2) ≥ 0.995; LOD is 0.1 mg/L, LOQ is 0.5 mg/L, % recovery with a range of(104,59 ± 1,73)%; repetition and reproducibility was expressed as % SBR <% KV Horwitz, MDL is 0.2745 mg/L. Based on the results of this study, infrared spectrophotometry methods can be used in determining oil and fat in seawater samples with valid results. Keywords: method validation, oil and greace, infrared spectrophotometry.